Mechanical properties of poly (lactic acid) (PLA)/clay nanocomposite - Mohd Shaifol, Hamid (2010)
Polymer nanocomposite (PNC) is a polymer or copolymer having dispersed in its nanoparticles. These may be of different shape (platelets, fibers, spheroids), then dimension must be in the range of 1 to 50 nm. PNC represent a new class of material alternative to the conventional filled polymers. Nanosized inorganic filler (at least one dimension) are dispersed in polymer matrix offering tremendous improvement in performance properties of the polymer. Poly (lactic acid) or polylactide (PLA) is biodegradable, thermoplastic, aliphatic polyester derived from renewable resources which is environmentally friendly, low density and cost and commercially available. In this project, the pure PLA will reinforce by adding the nanoclay type Cloisite® 30B in percentage of 1, 3 and 5 wt% inside the PLA matrix by melting processing using co-rotating twin-screw extruder at 210°C and 100rpm. The material was dried in the dryer at 80°C for 2 hours before through the melting process. The influence of nano particles in the PLA matrix was investigated on the morphology and mechanical properties. The Fourier transform infrared (FTIR) spectroscopy spectrum shows the attendance of Cloisite® 30B clay in the PLA matrix. Brinell harness test and tensile and tensile modulus properties result prove mechanical properties of PLA were improve after by dispersion of nanoclays.